Ecology of Two Selected Liana Species of Utility Value in a Lowland Rain Forest of Sri Lanka: Implications for Management - Kathriarachchi, Hashendra; Tennakoon, K. U.; Gunatilleke, C. V. S.; Gunatilleke, I. A. U. N.; Ashton, P. M. S. (My University, 2004)
Calamus ovoideus Thw. and Coscinium fenestratum Colebr. are economically important, naturally growing liana species in the disturbed habitats of lowland rain forests in Sri Lanka. Harvesting their mature stems has jeopardised their survival and led to dwindling populations. Growth performance, population sizes and the eco-physiology of these species were examined under three different canopy removal treatments and a closed canopy control of a Pinus caribaea buffer zone plantation of the Sinharaja forest. Population studies of Calamus spp. and C. fenestratum revealed that they survive and regenerate naturally in disturbed habitats compared to undisturbed forest. After nine years, both liana species grew poorly in the Pinus understorey (control) compared to the canopy removal treatments. During the study period, height increment of C. ovoideus was best in the three-row canopy removal treatment. In contrast to C. ovoideus, the eco-physiological features of C. fenestratum varied little among the canopy removal treatments, suggesting that they tolerate a wider range of light levels. The study revealed that both species could be successfully introduced to the Pinus caribaea buffer zones, degraded areas of lowland rain forests in Sri Lanka, in order to conserve them in the wild and manage them sustainably.